Combined Anthocleista vogelii and Alstonia boonei Stem Barks Extract Alleviates Hyperlipidaemia and Renal Malfunctions in Benign Prostatic Hyperplasia-Induced Rats - Robert Ikechukwu Uroko; Mercylyn Ezinne Uche; Paul Chukwuemaka Nweje-Anyalowu; Ikenna Obiwuru; Chinedu Aguwamba; Chinomso Friday Aaron (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2023)
Benign prostatic hyperplasia (BPH) is a urological disease prevalent among the ageing male population, which impairs the quality of life, including hyperlipidaemia and a decline in renal functions. Combining Anthocleista vogelii and Alstonia boonei stem bark extract has effectively managed BPH and its associated complications. This study evaluated the effects of a combined Anthocleista vogelii and Alstonia boonei stem bark extract (CAASBE) on the lipid profile and renal functions of rats induced benign prostatic hyperplasia with testosterone propionate injection. The study comprised five treatment groups, with groups 1 5 being the normal control, BPH control, standard control, BPH+200 mg/kg CAASBE, and BPH+400 mg/kg CAASBE, respectively. BPH was induced in the groups 2 4 rats by subcutaneous administration of testosterone propionate injection (5 mg/kg) for 28 days, and treatment with Finasteride and CAASBE were administered orally. The BPH control rats exhibited a significant (p < 0.05) increase in the total serum cholesterol, triacylglycerol (TAG), low-density lipoprotein cholesterol (LDL-C), urea, creatinine and significant (p < 0.05) decline in the serum high-density lipoprotein cholesterol (HDL-C) compared to the normal control. Conversely, treatment of the BPH rats with 200 and 400 mg/kg of CAASBE significantly (p < 0.05) reversed the altered total serum cholesterol, TAG, LDL-C, HDL-C, urea and creatinine to normal levels comparable to that of the normal control and standard control respectively. These findings show that CAASBE alleviates hyperlipidaemia and renal malfunctions in the BPH rats suggesting it could be effective in managing BPH complication.